Trade liberalisation, the income elasticity of demand for imports and growth in Latin America - Penélope Pacheco-López; A. P. Thirlwall (University of Kent, Department of Economics, 2005)
This paper applies the balance of payments constrained growth model to seventeen countries of Latin America over the period 1977-2002. The crucial parameter to estimate is the income elasticity of demand for imports which is done for Latin America as a whole, as well as for individual countries. As well as estimating over the whole period, the technique of rolling regressions is also used to test whether a trend increase can be discerned as a result of trade liberalisation. A trend increase is found for Latin America as a whole and for some individual countries, and the balance of payments equilibrium growth rate is a good predictor of growth performance in nine of the seventeen countries. There is no evidence that the balance of payments equilibrium growth rate has increased in Latin America as a result of trade liberalisation.
Keywords: C21; C22; F13; F32; F43; 330; Latin America; Trade Liberalisation; Growth; Balance of Payments; Außenhandelsliberalisierung; Importnachfrage; Einkommenselastizität; Exportinduziertes Wachstum; Lateinamerika